STUDI KEMAUAN MEMBAYAR PAJAK PADA WAJIB PAJAK ORANG PRIBADI YANG MELAKUKAN PEKERJAAN BEBAS (Kasus Pada KPP Pratama Tampan Pekanbaru) - Tedi Permadi; Azwir Nasir; Yuneita Anisma (Jurnal Ekonomi, 2013)
The purpose of this study was to examines the influence paying tax awareness,knowledge and understanding of tax regulation, a good perception of theeffectiveness of the taxation system, the confidence level of the systemadministration and law, moral norms on the willingness to pay taxes of anpersonal taxpayer who performs work free.Sampling techniques in the study was convenience sampling. To better representthe researchers took a sample of 98 respondents with Slovin formula calculations.This study uses quantitative methods, where the data obtained from distributingquestionnaires to the taxpayer who performs registered in KPP Pratama Tampan,Pekanbaru. Test statistic used is multiple linear regression test, and data obtainedwere processed using SPSS 17.0 statistical software.Based on the results of research that conducted, found the coefficient ofdetermination (Adj. R2) of 0.114. That means 11.4% of the willingness to paytaxes influenced by paying tax awareness, knowledge and understanding of taxregulation, a good perception of the effectiveness of the taxation system, theconfidence level of the system administration and law, moral norms. Theindependent variable in this study paying tax awareness, knowledge andunderstanding of tax regulation and moral norms had a significant influence onthe willingness to pay taxes. Then two independent variable a good perception ofthe effectiveness of the taxation system and the confidence level of the systemadministration and law doesn't influence on the willingness to pay taxes of anpersonal taxpayer who performs work freeKata Kunci : Willingness to pay taxes, paying tax awareness, knowledge andunderstanding of tax regulation, a good perception of theeffectiveness of the taxation system, the confidence level of thesystem administration and law, moral norms.